Phialoarthrobotryum bambusae sp. nov. (Chaetosphaeriaceae, Chaetosphaeriales), a new ascomycetous species of bambusicolous fungi from Meghalaya, India - Pratibha, J.; Bhat, Jayarama D.; Dawoud, Turki M.; Mao, A.a.; Ashish, Prabhugaonkar (Phytotaxa, 2026)
A new asexual morph synnematous ascomycetous fungus, Phialoarthrobotryum bambusae was found growing on decaying bamboo culms of Bambusa balcooa at an experimental botanical garden, Barapani, Meghalaya, India. The novel species Phialoarthrobotryum bambusae is characterized by synnematous conidiomata, monophialidic conidiogenous cells, and 3-septate, dark brown, smooth, slimy conidia. Analyses of partial ITS and LSU sequence data confirmed that our taxon forms an independent lineage within the Phialoarthrobotryum clade in the family Chaetosphaeriaceae (Chaetosphaeriales). A detailed characterization, accompanied by microphotographs and a phylogenetic tree depicting the position of the novel species, is provided in the paper.